2019
DOI: 10.1111/jfpp.14154
|View full text |Cite
|
Sign up to set email alerts
|

Oil extraction from blends of sunflower and black cumin seeds by cold press and evaluation of its physicochemical properties

Abstract: Oil seeds are usually pressed individually to extract the oil. In this study, blends of black cumin seed (BS) with sunflower seed (SS) were used to extract oil by cold pressing and the changes in physicochemical properties of the extracted oil were evaluated. Blending altered the fatty acid profile of the blends; with linoleic and oleic acids being the main fatty acids. As BS was increased in the blends, a significant increase (p < .05) in total pigments and phenolic contents in the extracted oils was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…(2010), Mazaheri et al. (2019), Ramadan and Moersel (2006), Ramadan et al. (2003, 2012), and Suri et al.…”
Section: Fat‐soluble Bioactives In Specialty Seed Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2010), Mazaheri et al. (2019), Ramadan and Moersel (2006), Ramadan et al. (2003, 2012), and Suri et al.…”
Section: Fat‐soluble Bioactives In Specialty Seed Oilsmentioning
confidence: 99%
“…Chlorophyll a and b contribute to the color of seed oils and are used for evaluating oil quality. Chlorophylls have been reported in all specialty seed oils except perilla seed and quinoa seed oils (Table 4) (Aachary et al., 2016; Aiello et al., 2020; Can‐Cauich et al., 2019; Górnaś et al., 2014; Mazaheri et al., 2019; Suri et al., 2019; Tuberoso et al., 2007; Uzunova et al., 2016; Zeb et al., 2017). Hemp seed oil contains the highest level of total chlorophyll (2.73 to 14.34 mg/100 g), followed by black cumin oil (0.31 to 7.56 mg/100 g), sesame seed oil (0.01 to 7.33 mg/100 g), pumpkin seed oil (0.60 to 4.92 mg/100 g), chia seed oil (2.21 mg/100 g), and flaxseed oil (tr‐0.68 mg/100 g) among the eight specialty seeds listed in Table 4.…”
Section: Fat‐soluble Bioactives In Specialty Seed Oilsmentioning
confidence: 99%
“…The highest PV (4.7 meq-O 2 /kg-oil) was obtained for PSO enriched with 10% GTL and the lowest amount (2.1 meq-O 2 /kg-oil) was obtained for PSO with 2.5% GTL. The addition of a sufficient not excessive amount of polyphenol-rich source to the oils with high susceptibility to oxidation can retard the oxidation and inhibit the propagation (Mazaheri et al, 2019a(Mazaheri et al, , 2019bPalit et al, 2008). However, the higher the polyphenol content, and also the higher the chlorophyll content the higher peroxyl radical production, and thus, oxidation was increased (Li et al, 2019;Rezvankhah et al, 2019).…”
Section: Peroxide Valuementioning
confidence: 99%
“…Drinić et al (2020) used pomegranate peel extract in PSO individually or with a combination with BHT to enhance the oxidative stability of the oil. Mazaheri et al (2019b) investigated the cold-press extraction of sunflower and black cumin seeds and reported that seeds mixing caused an increase in oxidative stability, which increased from 6.78 to 9.69 h.…”
Section: Introductionmentioning
confidence: 99%
“…Perilla oil from perilla seed was extracted by cold-pressed method (Screw Press Model 85 mm) in two batches (1 kg in one batch) at 10 MPa for 20 min from a commercial mill (Mohan oil mill) in New Delhi, India. The extracted oil was filtered through muslin cloth and Whatman no.2 filter paper to remove the impurities and stored in a sealed dark amber bottle until further use [14].…”
Section: Oil Extractionmentioning
confidence: 99%